2020
DOI: 10.3390/metabo10010020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Serum Metabolomic Profiles of Growing Pigs Induced by Intravenous Infusion of Sodium Butyrate

Abstract: This study aimed to explore the dynamic changes in metabolite profiles and metabolism pathways in the serum of growing pigs by intravenous infusion of sodium butyrate (SB). Fourteen crossbred growing barrows (BW = 23.70 ± 1.29 kg) fitted with jugular cannula were randomly allocated to the SB and control (Con) groups, each group consisted of seven replicates (pens), with one pig per pen. At 9:00 of each day during the experimental period, pigs in the SB group were infused with 10 mL of SB (200 mmol/L, pH 7.4, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…SCFAs were the main end-products of microorganisms fermenting carbohydrates, which are generally believed to have a benefit to host health ( 43 ). Specifically, butyrate, as one of the most important SCFAs, has extensive effects on improving immunity and intestinal health and promoting host metabolism ( 3 , 44 ). In the present study, we found that TRF has increased the concentration of butyrate which indirectly reflected that TRF could improve host metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFAs were the main end-products of microorganisms fermenting carbohydrates, which are generally believed to have a benefit to host health ( 43 ). Specifically, butyrate, as one of the most important SCFAs, has extensive effects on improving immunity and intestinal health and promoting host metabolism ( 3 , 44 ). In the present study, we found that TRF has increased the concentration of butyrate which indirectly reflected that TRF could improve host metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a considerable amount of reference highlighted the contributions of the type, quantity, and composition of nutrients intake to host health and metabolism both on animals and human beings (1)(2)(3)(4). By contrast, there are fewer studies concerning the effects of feeding patterns on health and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Partial least squares discriminant analysis (PLS-DA) was carried out to further explore the differential metabolites among the treatment groups. Pathway analysis and metabolite set enrichment analysis were performed on metabolites that had a Variable Importance in Projection (VIP) score > 1 [ 76 , 77 ]. The following criteria were used to identify the specific compounds responsible for the differences: VIP > 1, fold change > 2, and FDR < 0.2.…”
Section: Methodsmentioning
confidence: 99%
“…In fruit fly Drosophila melanogaster , it has been reported that adding sodium butyrate to the diet can effectively reduce the susceptibility or short-term mortality risk during aging [ 5 ]. Thus, sodium butyrate plays a non-negligible role in the dynamic relationship between diet, gut microbiome composition, and metabolic health for all animals [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%